Examining Religious Commodification in Aniocha South, Delta State, Nigeria: Theological Implications and Ethical Challenges - Benson Ndidi Menimor (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Religion has historically functioned as a moral, spiritual, and communal institution in Aniocha South, Delta State, Nigeria. Traditional religious practices, particularly sacrifice, served as sacred mechanisms for maintaining harmony among humanity, the ancestors, and the divine realm. However, contemporary socio-economic realities, globalization, and the proliferation of charismatic religious movements have contributed to the commodification of religion, wherein sacred beliefs, rituals, and symbols are transformed into marketable products and services. This study examines the phenomenon of religious commodification in Aniocha South and its implications for sacrificial practices, spiritual authority, and communal morality. The study adopts a qualitative, library-based research design, drawing on documentary and textual analysis of secondary theological, anthropological, and sociological sources alongside biblical texts, interpreted through a hermeneutical and thematic method. Using theological, anthropological, and ethical approaches, the paper argues that the commercialization of religion has facilitated the abuse of sacrifice and enabled exploitative practices by fraudulent spiritual leaders. The study further contends that religious commodification undermines both indigenous ethical traditions and biblical teachings on sacrifice, worship, and leadership. It concludes by advocating for a contextual theological reformation grounded in ethical accountability, theological literacy, and communal responsibility. In doing so, the study addresses a gap in existing scholarship, which has largely examined religious commodification within broader African contexts without adequately accounting for how local cultural realities in Aniocha South shape and sustain its commodified forms.